Implementasi Karakter Handep Hapakat Pada Program Makan Bergizi Gratis (MBG) dI SMPN 11 Palangka Raya - Pebrianti, Anisa; Silalahi, Juli Natalia; Rusmanto, Joni; Adiwijaya, Saputra; Ulfaritha Lapalu, Ester Sonya; Sontoe, Sontoe; Anam, M. Syaeful; Saragih, Osi Karina; Kaharap, Yorgen; Damayanti, Elia (Equilibrium: Jurnal Pendidikan, 2026)
Implementation of strategic national policies at the school level often faces adaptation and acceptance challenges in local institutions, particularly in regions rich in local wisdom such as Central Kalimantan. This study was conducted to analyze the integration of the local wisdom value handep hapakat (cohesion and mutual assistance) within the Free Nutritious Meal Program (MBG) at SMPN 11 Palangka Raya. This background prompted a study focusing on the socio-cultural dimension of MBG, which has been effectively running for two months since September 1, 2025. The primary objective of the research was to analyze the implementation of handep hapakat, identify the roles of actors (teachers, students, parents) in the program's sustainability, and examine socio-cultural barriers. The study employed a descriptive qualitative approach with data collected through in-depth interviews with teachers and students. Thematic analysis was conducted using a sociological framework encompassing Solidarity (Durkheim), Inequality (Marx), and Habitus/Social Capital (Bourdieu). The main findings indicate that Handep Hapakat serves as a catalyst for mechanical solidarity (Durkheim). This is evidenced by students' spontaneous initiative in logistics mutual cooperation and the collective meal as a cohesion-strengthening social ritual. Teachers play a central role as guarantors of equitable distribution, ensuring consistent and fair portions, thereby effectively mitigating the risk of access inequality (Marx) within the school environment. Although a clash of taste habitus (menu boredom) was observed, the Handep Hapakat value is capitalized as Social Capital (Bourdieu), realized through the mechanism of sharing leftover food (anti-waste). The active role of teachers in shaping responsible habitus is also crucial. It is concluded that the success of the MBG program at SMPN 11 Palangka Raya relies on the harmonious integration between national policy and local values. The implementation supported by Handep Hapakat yields a Sustainable Implementation Model that not only achieves nutritional goals but significantly reinforces students' social character, collective responsibility, and social capital. The scientific contribution of this research confirms the important role of local culture in the adaptation and effectiveness of public policies at the grassroots level.